1997
DOI: 10.1128/jb.179.13.4232-4238.1997
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DL-2-haloacid dehalogenase from Pseudomonas sp. strain 113: gene cloning and structural comparison with D- and L-2-haloacid dehalogenases

Abstract: DL-2-Haloacid dehalogenase from Pseudomonas sp. strain 113 (DL-DEX) catalyzes the hydrolytic dehalogenation of both D-and L-2-haloalkanoic acids to produce the corresponding L-and D-2-hydroxyalkanoic acids, respectively, with inversion of the C 2 configuration. DL-DEX is a unique enzyme: it acts on the chiral carbon of the substrate and uses both enantiomers as equivalent substrates. We have isolated and sequenced the gene encoding DL-DEX. The open reading frame consists of 921 bp corresponding to 307 amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
59
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 25 publications
5
59
1
1
Order By: Relevance
“…This applies to the dehalogenations of both enantiomers of 2-haloalkanoic acids because the results obtained for both enantiomers were virtually the same. We previously reported that DL-DEX 113 has a single and common catalytic site for both L-and D-enantiomers based on a site-directed mutagenesis experiment and kinetic analysis (17). This conclusion is supported by our present data showing that the enzymatic dehalogenations of both enantiomers proceed through the same mechanism as shown in Fig.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…This applies to the dehalogenations of both enantiomers of 2-haloalkanoic acids because the results obtained for both enantiomers were virtually the same. We previously reported that DL-DEX 113 has a single and common catalytic site for both L-and D-enantiomers based on a site-directed mutagenesis experiment and kinetic analysis (17). This conclusion is supported by our present data showing that the enzymatic dehalogenations of both enantiomers proceed through the same mechanism as shown in Fig.…”
supporting
confidence: 81%
“…2), and found that it is similar to that of D-DEX from Pseudomonas putida AJ1 (17). We also showed that DL-DEX 113 has a single and common catalytic site for both D-and L-enantiomers based on a site-directed mutagenesis experiment and kinetic analysis (17). In the present study, we analyzed the reaction mechanism of DL-DEX 113 by means of 18 O incorporation experiments, and found that the reaction does not involve the formation of an enzyme-substrate ester intermediate.…”
mentioning
confidence: 99%
See 3 more Smart Citations